Boosting Elementary School Students' Listening Skills through specially Created Songs - Ni Made Ratminingsih (Universitas Pendidikan Ganesha, 2011)
Listening skill is one of the language skills which has to be mastered by language learners. It is the first and foremost skill which becomes the foundation for further skills. For those young language learners who are in the phase of development of the so-called concrete operation, and have short span of concentration, language learning will be more effective if it is designed and wrapped up in the form of learning while playing. Song is one of the teaching techniques to assist them to optimize learning. Songs do not only make them happy to learn, increase concentration, enhance security and comfortable feeling, raise interests, but more importantly various vocabulary, grammar, pronunciation, and language expressions can be contextualized as to support language acquisition. This article aims at sharing theoretical insight and pedagogical practices on the use of special composed songs to accomplish listening instruction for fourth graders of elementary school.